Concepções de ciência dos professores da área da saúde e as dinâmicas curriculares de formação profissional da Universidade do Estado do Pará - RAIOL, Alessandra Nepomuceno (Universidade Federal do Pará, 2017)
This paper investigates the concepts of science of the teachers and the curriculum dynamics of professional training in health of the University of Pará State. It is an epistemological study, i.e., it performs a critical study of science regarding it as product and process, in order to analyze critically the injunctions of scientific knowledge to society. The problem is summarized in the question: How do the professors' conceptions of science interfere with the new dynamics of vocational training curricula in health? It is a qualitative descriptive research, relies on Gamboa Paradigm, construction template of knowledge for educational research and is based on the materialist dialectic that guides their synthesis in the movement of the struggle of opposites in the context of society. The methodological procedures used were bibliographical and documentary research. To this end, we anchor our studies of science in theoretical as Bachelard (1996), Thomas Kuhn (1998), Japiassú (2006), Boaventura de Souza Santos (1998) and Edgar Morin (2002, 2010). Regarding the curriculum studies, we rely on the contributions of Thomas Tadeu (2005) and Goodson (2012), which point new outlets, advances and possibilities for the school and the curriculum, as these fields of knowledge are interwoven with epistemology and the historical-social context, besides Moreira; Silva (2006) and Sancristán (2000) students of curriculum theory and its relation to culture, politics and ideology. And we still use curricular authors who discuss the issue in health such as Maia (2014), Mattos (2004, 2011), among others. As a result, we identified that the Cartesian paradigm permeates the concept of science of the teachers. However they realize the existence of the new paradigm of complexity and completeness, both in the context of science as in the context of health education. This coexistence of paradigms hinders how teachers understand the concepts related to the profession restructuring, while providing recognize the new curriculum dynamics as possibility to contribute to training more in line with the needs of society, then a professional more critical of its performance and its context. An education that integrates science, culture and technology. Finally, as factors that may contribute to the understanding, and for the teachers involvement in these dynamics, we noted the continuous assessment, the continuing education guided by discussions of epistemology and the new science paradigms as essential elements to the teaching practice, the collective construction of Pedagogical Project, the institutional support, the overcoming of simplistic visions and the teaching individualism.